Design and Development of 220kV SF6 Gas Insulated GIS Actual Testing Platform. (September 2020) - Zhang, Shiling
Abstract: To simulate the performance parameters of SF6 gas insulated AC GIS equipment under normal and failure condition in the laboratory environment, and the development trend of characteristic parameters such as partial discharge and SF6 gas decomposition can be monitored periodically and quantitatively, the 220kV SF6 gas insulated GIS type test platform is designed and developed. The test platform is in accordance with GIS specifications used in substation, including gas insulated circuit breaker and other typical GIS equipment. The external voltage is realized by the series resonant circuit. The paper starts from the design of the GIS bus and the solid insulation structure, and the three-dimensional E-field distribution characteristics of the solid insulator are simulated and analyzed. The hardware installation of the partial discharge measurement and SF6 gas decomposition monitoring on GIS model test platform are discussed. Through design and development of 220kV SF6 gas insulated GIS type-test platform, the feasibility of the structure design of GIS bus and the solid insulation are verified, it provides theoretical and practical basis for the operation and maintenance of SF6 gas insulated GIS equipment.